Performance Study of Cultural Algorithms Based on Genetic Algorithm with Single and Multi Population for the MKP - Silva, Deam James Azevedo da; Teixeira, Otávio Noura; Oliveira, Roberto Célio Limão de (IntechOpen, 2012)
None